Intraspinal AAV Injections Immediately Rostral to a Thoracic Spinal Cord Injury Site Efficiently Transduces Neurons in Spinal Cord and Brain - Michelle C Klaw; Chen Xu; Veronica J Tom (Elsevier, 2013)
In the vast majority of studies utilizing adeno-associated virus (AAV) in central nervous system applications, including those published with spinal cord injury (SCI) models, AAV has been administered at the level of the cell body of neurons targeted for genetic modification, resulting in transduction of neurons in the vicinity of the injection site. However, as SCI interrupts many axon tracts, it may be more beneficial to transduce a diverse pool of supraspinal neurons. We determined if descending axons severed by SCI are capable of retrogradely transporting AAV to remotely transduce a variety of brain regions. Different AAV serotypes encoding the reporter green fluorescent protein (GFP) were injected into gray and white matter immediately rostral to a spinal transection site. This resulted in the transduction of thousands of neurons within the spinal cord and in multiple regions within the brainstem that project to spinal cord. In addition, we established that different serotypes had disparate regional specificity and that AAV5 transduced the most brain and spinal cord neurons. This is the first demonstration that retrograde transport of AAV by axons severed by SCI is an effective means to transduce a collection of supraspinal neurons. Thus, we identify a novel, minimally invasive means to transduce a variety of neuronal populations within both the spinal cord and the brain following SCI. This paradigm to broadly distribute viral vectors has the potential to be an important component of a combinatorial strategy to promote functional axonal regeneration.